The Bangladesh economy in transition - Quibria, M. G. (Muhammad Ghulam) (Oxford University Press, 1997)
Revised version of papers presented in a conference held in Bangladesh, 1993, organized by the Asian Development Bank in collaboration with the Academy for Planning and Development, Bangladesh.